2019
DOI: 10.3390/ijms20153661
|View full text |Cite
|
Sign up to set email alerts
|

Culture Dependent and Independent Analysis of Potential Probiotic Bacterial Genera and Species Present in the Phyllosphere of Raw Eaten Produce

Abstract: The plant phyllosphere is colonized by a complex ecosystem of microorganisms. Leaves of raw eaten vegetables and herbs are habitats for bacteria important not only to the host plant, but also to human health when ingested via meals. The aim of the current study was to determine the presence of putative probiotic bacteria in the phyllosphere of raw eaten produce. Quantification of bifidobacteria showed that leaves of Lepidium sativum L., Cichorium endivia L., and Thymus vulgaris L. harbor between 103 and 106 DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…can occur on asparagus, the availability of a rapid and safe species-specific diagnosis tool would be useful. Nowadays, the identification of microbial pathogens is routinely performed using matrix-assisted laser desorption ionisation time-of-flight mass spectrometry (MALDI-TOF MS, Bruker Daltonik, Bremen, Germany ), especially for bacterial iso lates [ 36 ]. Additionally, mass-spectrometry-based approaches have also been applied successfully for the identification and differentiation of Fusarium species based on spore protein profiles [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…can occur on asparagus, the availability of a rapid and safe species-specific diagnosis tool would be useful. Nowadays, the identification of microbial pathogens is routinely performed using matrix-assisted laser desorption ionisation time-of-flight mass spectrometry (MALDI-TOF MS, Bruker Daltonik, Bremen, Germany ), especially for bacterial iso lates [ 36 ]. Additionally, mass-spectrometry-based approaches have also been applied successfully for the identification and differentiation of Fusarium species based on spore protein profiles [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of yeast, LAB, and Bifidobacterium sp., generally regarded as health-supporting microbes, makes this aforesaid a probiotic food. The succession of these organisms from the plant phyllosphere [ 23 ] to the food was first established by this study. These microbes are wild, biologically active, and not altered by the atmospheric agents [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas was also abundant in our samples, but Erwinia could not be detected. The most abundant phyllosphere genus detected in the present study was Lactobacillus , a group of probiotic bacteria that have also been detected in the phyllosphere of raw eaten produce [ 44 ]. This genus has not previously been associated with the sugar beet, but Barbu et al [ 45 ] have shown that Lactobacilli , when sprayed on sugar beet leaves, can successfully colonize the phyllosphere.…”
Section: Discussionmentioning
confidence: 99%